Les romans de Gilles Rozier ou les langues et la post-mémoire juives sorties de l’impasse du silence - Sadkowski, Piotr (Wydawnictwo Naukowe UAM, 2013)
The aim of the article is to provide a reading of Gilles Rozier’s novels in the context of the phenomenon of Jewish postmemory (Hirsch), which in recent literature acquires a new dimension. The texts selected for disscussion exemplify the return to narrative and to the subject in contemporary novel and signal a new approach to postmemory employed by the third generation of survivors, participants of the Jewish revival. In Rozier’s novels, and in texts by other contemporary writers (e.g., Daniel Mendelsohn in the USA or Piotr Paziński in Poland), while the memory of WWII does not disappear, the focus most often falls on the narrative of Jewish life before and after the Holocaust. Postmemory exists in those texts in the form of the transmission of the word, repossession of the language of ancestors, cultural continuity rather than silence and separation, which characterised the output of earlier generations of writers (such as, for example, Georges Perec).
Gilles Rozier’s novels or Jewish languages and postmemory transcend the impasse of silence
Keywords: Jewishness; postmemory; languages; survivors; narratable